Sodium-calcium exchange - Reeves, John (Henry Stewart Talks, 2007)
The definition and thermodynamic driving forces for Na/Ca exchange and the historical development of the field, The molecular biology of Na/Ca exchange family members, The regulation of Na/Ca exchange, The physiological functions of Na/Ca exchange in cardiac physiology, hypertension and higher neural functions